The Utilization of SQ3R Method to Enhance English Reading Skills: Students’ Voices in The Indonesian Higher Education Context - Wahyuningsih, Sri; Nafisah, Putri; Mulyono, Nono; Hidayat, Yusuf (International Journal Corner of Educational Research, 2023)
The problem mostly experienced by EFL students is the assumption of difficulty in reading English texts. Thus educators are always looking for the best teaching approach methods to develop skills, especially in reading skills.  The present study mainly describes the students’ voices about using SQ3R in improving reading skills in the Indonesian higher education context. This study belongs to a descriptive qualitative study. Data were gathered through observation and interviews with students. The results of the study demonstrate that most students believe that the existence of the SQ3R method can have an impact on the learning process of students. It has benefits including improving students' reading comprehension skills, increasing high curiosity, and being able to provide experiences of understanding discourse more easily.